Non-invasive brain stimulation for the treatment of brain diseases in childhood and adolescence: state of the art, current limits and future challenges - Vicario, Carmelo M.; Nitsche, Michael A. (Frontiers in Systems Neuroscience, 2013)
In the last decades interest in application of non-invasive brain stimulation for enhancing neural functions is growing continuously. However, the use of such techniques in pediatric populations remains rather limited and mainly confined to the treatment of severe neurological and psychiatric diseases. In this article we provide a complete review of non-invasive brain stimulation studies conducted in pediatric populations. We also provide a brief discussion about the current limitations and future directions in a field of research still very young and full of issues to be explored.